Peningkatan Kemampuan Analisis Struktur Surat Lamaran Kerja dengan Media Puzzle pada Siswa Kelasn XII di SMK 5 - Nadia Husna Safitri; Kaswadi Kaswadi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article focuses on improving the ability to analyze the structure of job application letters by using puzzle media in grade XII students at SMK 5 Surabaya. This research was conducted because students often have difficulty in analyzing the text of a job application letter, even though this material is very important for daily life, especially in finding a job. The research method used is Classroom Action Research (PTK) which consists of two cycles. Each cycle includes planning, execution, observation, and reflection. In this study, puzzle media is used as a learning tool to improve students' analytical thinking skills. The results showed that the use of puzzle media significantly improved students' analytical ability from pre-cycle to second cycle, with the level of learning completeness increasing from 34.29% in pre-cycle to 87.68% in second cycle. Puzzle media is effective in improving students' analytical skills, and it is recommended to be applied to other subjects with appropriate learning strategies.